CO2 heat pump for waste heat recovery and utilization in dairy industry with ammonia based refrigeration. (June 2017) - Singh, Simarpreet; Dasgupta, M.S.
Highlights: A CO2 heat pump system with IHX for combined heat recovery and water heating application is proposed for a dairy industry. Total fuel cost is reduced by 45.7%, CO2 emission is reduced by 33.8% and use of ground water for condenser is eliminated. Economic analysis shows payback period for the proposed CO2 heat pump system with IHX is approximately 40 months. Abstract: Based on field data from a medium scale ammonia based milk refrigeration plant located in northern India, a trans-critical CO2 heat pump system with IHX is conceptualized for waste heat utilization. The waste heat is utilized to pre-heating the boiler feed water and thereby reduces energy consumption. A thermodynamic model of the refrigeration system is built and simulated for year-round field data. In this study, the condenser of the ammonia based refrigeration system is coupled with the evaporator of the proposed CO2 heat pump which is maintained at 20 °C year-round. The heat pump delivers heat at about 70 °C to pre-heat the boiler feed water drawn from underground source and is available in temperature range of 25 °C to 29 °C year-round. Thus, the CO2 heat pump performance is essentially independent of variation in ambient temperature. We reported reduction in CO2 emission and reduction in total energy cost by approximately 45.7% and 33.8% respectively. Economic analysis shows the payback period (PBP) is about 40 months.